1996
DOI: 10.1074/jbc.271.38.23161
|View full text |Cite
|
Sign up to set email alerts
|

Nonhydrolyzable Analogues of GTP Activate a New Na+ Current in a Rat Mast Cell Line

Abstract: Whole-cell patch clamp experiments were performed to examine the effects of the nonhydrolyzable GTP analogue, guanosine 5-3-O-(thio)triphosphate, on membrane currents in rat basophilic leukemia cells. Guanosine 5-3-O-(thio)triphosphate activated an inward sodium current. This current had a new permeability sequence to monovalent cations and a different pharmacological profile to that of other characterized Na ؉ channels. Long hyperpolarizing steps revealed that the current declined during the pulse, and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(16 reference statements)
1
13
0
Order By: Relevance
“…Dialysis with 250 M GTP␥S did not affect slow inactivation either (inactivation of 77 Ϯ 9%). Later on in these same cells (after a 5-10-min recording), the GTP␥S-dependent Na ϩ current activated (14), demonstrating that the GTP␥S was active under these conditions.…”
Section: Investigation Into the Mechanism Of Camentioning
confidence: 74%
“…Dialysis with 250 M GTP␥S did not affect slow inactivation either (inactivation of 77 Ϯ 9%). Later on in these same cells (after a 5-10-min recording), the GTP␥S-dependent Na ϩ current activated (14), demonstrating that the GTP␥S was active under these conditions.…”
Section: Investigation Into the Mechanism Of Camentioning
confidence: 74%
“…First, it increased the electrical driving force for Ca 2+ entry through CRAC channels. Second, the Na + current activated by GTP[γ-S] is largely inactive at this potential [20]. The slowly developing Na + current would interfere with the capacitance measurements by inducing a large increase in membrane conductance.…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were made on planar lipid bilayers containing cloned epithelial sodium channels (4, 7). In addition, interaction of actin with epithelial channels was reported to modulate considerably the intrinsic channel characteristics including conductance and selectivity.Along with epithelial amiloride-sensitive sodium channels, novel non-voltage-gated sodium-selective channels insensitive to amiloride (up to 100 M) and to tetrodotoxin have been described in different non-excitable cells, particularly in vascular smooth muscle cells (8), macrophages (9), and carcinoma (10) and leukemia cells (11)(12)(13). In these studies, single current measurements in different patch configurations showed that conductance, selectivity, and gating properties of the novel family of sodium channels proved to be very similar to those of the epithelial channels (14).…”
mentioning
confidence: 99%